(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Understanding the relationship between a subordinate and manager develops over time has been a critical matter both for academics and for business. In both academic journals and industry publications, some writers have argued that the relationship is driven by perceptions of fairness and treatment, and that developing the relationship can lead to better performance. Research on the impact of technology on work patterns and the work environment that I conducted with a major corporate research laboratory led to some relevant insights. Leading-edge firms around the globe were identified, their senior management teams interviewed and work patterns observed. Others have argued that higher performers get better treatment and resources, which results in superior relationships with their managers. There is really no clear answer of what comes first—perceptions of fairness, satisfaction with the supervisor, or job performance—and which leads to which.